The social animal - Aronson, Elliot; Aronson, Joshua (New York : Worth Publishers, 2012)
'The Social Animal' offers an introduction to modern social psychology. Elliot Aronson probes the patterns and motives of human behaviour, covering topics as diverse as conformity, obedience, politics, and advertising.
1. What is social psychology? -- 2. Conformity -- 3. Mass communication, propaganda, and persuasion -- 4. Social cognition -- 5. Self-justification -- 6. Human aggression -- 7. Prejudice -- 8. Liking, loving, and interpersonal sensitivity -- 9. Social psychology as a science -- Glossary.
Includes bibliographical references (p. [438]-485) and indexes.
Keywords: Social psychology